JUVENTUDES EXCLUÍDAS DA ESCOLA NO MUNICÍPIO DE GUARAPUAVA/PR: REPRESENTAÇÕES SOCIAIS DE EDUCADORES SOBRE A EVASÃO NO ENSINO MÉDIO - PEPLINSKI, EMANUELLY (2020)
This research aims to understand school dropout in public high school from the social representations of principals, pedagogues and teachers from four state schools in the city of Guarapuava/PR, totaling 26 subjects. Dropout is characterized as student's exit from the education system, it is a complex and multidetermined phenomenon which is more present in high school than in other stages of basic education. To achieve the proposed objectives, case study methodology was used, with an exploratory-descriptive qualitative approach. Semi-structured interviews were carried out, analyzed by the data analysis methodology. To corroborate with the analysis, Moscovici's Social Psychology was used, which considers social representations to be a system of values and practices that aims to organize reality to control it and enable communication within a community, together with authors from Socio-Historical Psychology and classical and contemporary materialism authors, researchers of the functioning and dynamics of capitalist society, from a historical perspective to situate the outline of the research and the characteristics of the conjuncture in which they are inserted. Thus, the literature demonstrates that many factors are related to school dropout, from individual, family, scholar, to social ones. It is also among the people who most evade that those who already suffer exclusion in other social spheres are: poor, black and indigenous people, people from the rural area, with disabilities and learning difficulties, with a history of school failures and informal work. The following categories were raised: definition of school dropout, perception of dropout, related factors, profile of dropout student, dropout reflexes, actions in response to dropout, and prevention possibilities. It is possible to understand that contradictions that appear in the literature are also present in educators‟ speeches. The school has been highly charged with regard to controlling and combating dropout, especially with the new absenteeism and dropout control tools available. Educators reflect that greater participation by the family in the school life of young people is required, as well as effective work by the Youth Protection Services. However, many of the intercurrent factors related to dropout are social, that is, the school alone is not able to fulfill these demands, this leads to frustration in relation to educators‟ work and reflects in the school structure: with the reduction of investments and closing of classes/shifts. It is important to raise the awareness of communities and students, as well as to fight for public policies that support and guarantee the permanence of these students who do not see meaning or place in school for them, because without the necessary conditions this youth is being excluded from their right to integral and quality education.